2021
DOI: 10.1021/acsmedchemlett.0c00532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 5-(Trifluoromethyl)-1,2,4-oxadiazole-Based Class IIa HDAC Inhibitors for Huntington’s Disease

Abstract: Using an iterative structure−activity relationship driven approach, we identified a CNS-penetrant 5-(trifluoromethyl)-1,2,4-oxadiazole (TFMO, 12) with a pharmacokinetic profile suitable for probing class IIa histone deacetylase (HDAC) inhibition in vivo. Given the lack of understanding of endogenous class IIa HDAC substrates, we developed a surrogate readout to measure compound effects in vivo, by exploiting the >100-fold selectivity compound 12 exhibits over class I/IIb HDACs. We achieved adequate brain expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The most surprising finding is the significant loss of affinity of 20 and 21 . Our data is in line with a recent report which also demonstrated that replacing the trifluoro-with difluoro-moiety to significantly reduce the affinity to class-IIa HDACs [ 25 ]. The high selectivity of TFMO to class-IIa HDACs combined with reducing its affinity to class-I/IIb HDACs can be explained by the relatively larger size (volume) of catalytic cavity of class-IIa HDACs due the substitution of His976 (class IIa) for Tyr306 (class-I/IIb) in the catalytic site [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The most surprising finding is the significant loss of affinity of 20 and 21 . Our data is in line with a recent report which also demonstrated that replacing the trifluoro-with difluoro-moiety to significantly reduce the affinity to class-IIa HDACs [ 25 ]. The high selectivity of TFMO to class-IIa HDACs combined with reducing its affinity to class-I/IIb HDACs can be explained by the relatively larger size (volume) of catalytic cavity of class-IIa HDACs due the substitution of His976 (class IIa) for Tyr306 (class-I/IIb) in the catalytic site [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Compound 78 had preference for class IIa HDACs and inhibited recombinant isoforms with 157 nM (HDAC4), 97 nM (HDAC5), 43 nM (HDAC7), and 23 nM (HDAC9), as well as 8.2 µM (HDAC6) and 4.2 µM (HDAC8). Most recently, inspired by the work of Lobera et al [ 153 ] and Guerriero et al [ 154 ], Stott et al [ 155 ] searched for CNS-penetrant class IIb HDACis and identified the class IIb-selective compound 79 for use in preclinical models of Huntington’s disease. Starting from compound 80 from Hebach et al [ 156 ], an SAR study was conducted by derivatizing the TFMO group, the linker, and the cap group [ 156 ].…”
Section: Trifluoromethyloxadiazole (Tfmo) Warheadsmentioning
confidence: 99%
“…The first series incorporated a hydroxamic acid-based inhibitor, analogous to the CNS penetrant class IIa HDAC inhibitor developed by Luckhurst et al , 72 which was appended via a PEG linker to a VHL E3 ligase ligand, with three different lengths investigated. The second series of PROTACs were based on a trifluoromethyl oxadiazole (TFMO) HDAC inhibitor, reported previously by Scott et al 73…”
Section: Protacs Targeting Hdac4mentioning
confidence: 99%